Design of decolorization of methylene blue mixed synthetic wastewater via modified vermiculite using Taguchi method - Sahra Dandil (Adsorption Science & Technology)
In this study, vermiculite was modified and used in the decolorization of wastewater containing methylene blue. Taguchi experimental design method was applied to the process. An L 16 orthogonal array was obtained according to Taguchi design by determining five factors effective on the process (pH, time, concentration, amount, and temperature) and four levels of these factors. Taguchi method determined concentration as the most effective factor. It suggested pH 3, 60 min, 5 mg.L −1 , 2 g.L −1 and 50°C as optimum conditions. Equilibrium studies were carried out with Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich isotherm models, and the process was found to be compatible with the Langmuir ( R 2  = 0.9103) and Dubinin–Radushkevich ( R 2  = 0.9344) model. It was determined that the material had a maximum capacity of 9.60 mg.g −1 . In kinetic studies conducted with pseudo-first-order, pseudo-second-order, and intraparticle diffusion models, the process complied with the pseudo-first-order ( R 2  = 0.9903) and intraparticle diffusion ( R 2  = 0.9811) models. The chemical composition was determined, and phase analysis was performed. By Branuer–Teller–Emmet analysis, it was determined that vermiculite exhibited a higher surface area (8.00 m 2 /g) by modifying it. It was seen as a result of Fourier transform-infrared spectroscopy analysis that the active functional groups were similar for vermiculite and modified vermiculite. Mass losses of both materials were evaluated by thermal analysis.